(untitled) (International Seven Journal of Multidisciplinary, 2023)
The role of commercial directors in the real estate industry requires a balance between strategic marketing planning and effective sales monitoring. This article explores how directors coordinate marketing plans, track sales goals, and collaborate with sales managers to drive successful outcomes, particularly in regional property launches. Drawing from academic research and industry practices, as well as examples of successful regional real estate projects, the study highlights how structured marketing planning combined with data-driven sales monitoring enhances performance, strengthens market positioning, and creates measurable business growth.